A minireview on covalent organic frameworks as stationary phases in chromatography - Gavara, Raquel; Royuela, Sergio; Zamora, Félix (Frontiers in Chemistry, 2024)
Advances in the design of novel porous materials open new avenues for the development of chromatographic solid stationary phases. Covalent organic frameworks (COFs) are promising candidates in this context due to their remarkable structural versatility and exceptional chemical and textural properties. In this minireview, we summarized the main strategies followed in recent years to apply these materials as stationary phases for chromatographic separations. We also comment on the perspectives of this new research field and potential directions to expand the applicability and implementation of COF stationary phases in analytical systems.